2018
DOI: 10.1016/j.joi.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of zero-inflated data: An empirical analysis of a new indicator family and its use with altmetrics data

Abstract: Recently, two new indicators (Equalized Mean-based Normalized Proportion Cited, EMNPC;Mean-based Normalized Proportion Cited, MNPC) were proposed which are intended for sparse scientometrics data. The indicators compare the proportion of mentioned papers (e.g.on Facebook) of a unit (e.g., a researcher or institution) with the proportion of mentioned papers in the corresponding fields and publication years (the expected values). In this study, we propose a third indicator (Mantel-Haenszel quotient, MHq) belongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…The reported Spearman coefficient for the correlation of Twitter counts and REF quality scores amounted to r s = 0.07. The results of this study accords also to the results of Bornmann and Haunschild [ 38 ] who investigated the relationship between altmetrics and assessments by peers. They found using the new MHq performance indicator which is especially suited for zero-inflated altmetrics data that “the relationship between altmetrics and peers’ assessments (one aspect of scientific quality) is not as strong as the relationship between peers’ assessments and citations”.…”
Section: Discussionsupporting
confidence: 90%
“…The reported Spearman coefficient for the correlation of Twitter counts and REF quality scores amounted to r s = 0.07. The results of this study accords also to the results of Bornmann and Haunschild [ 38 ] who investigated the relationship between altmetrics and assessments by peers. They found using the new MHq performance indicator which is especially suited for zero-inflated altmetrics data that “the relationship between altmetrics and peers’ assessments (one aspect of scientific quality) is not as strong as the relationship between peers’ assessments and citations”.…”
Section: Discussionsupporting
confidence: 90%
“…Pairwise correlations can give useful insights into relationships between different metrics, but for the purposes of reducing data into composite scores it is helpful to understand the shared variance between multiple metrics. The exploratory factor analysis in our study produced findings consistent with those reported in previous literature [10][11][12][13]. Separating articles into those that were older (1H) and younger (2H) showed that citations (including policy and guideline mentions) and Mendeley readers consistently grouped into one factor; news, blogs, Wikipedia, and F1000Prime mentions grouped into a second factor; and Twitter (and, usually, Facebook) mentions comprised a third factor.…”
Section: Rationale For the Three Component Scoressupporting
confidence: 89%
“…For zero-inflated data, it is not possible to use methods for field normalization that are usually applied in bibliometrics (methods based on mean citations or citation percentiles; Bornmann et al, 2013). Since Bornmann and Haunschild (2018) and 2 The explanation of the MHq indicator has been mainly adopted from Bornmann and Haunschild (2018) and Haunschild and Bornmann (2018). Note: WoS papers (unit 0; neither accepted, nor rejected for funding), papers published by rejected applicants (unit 1), and papers published by accepted applicants (unit 2).…”
Section: Mantel-haenszel Quotient (Mhq)mentioning
confidence: 99%
“…The MH analysis results in a summary odds ratio for multiple 2 × 2 cross tables, which Bornmann and Haunschild (2018) and Haunschild and Bornmann (2018) name MHq. For the comparison of the papers published by the applicants with reference sets in view of impact, the 2 × 2 cross tables (which are pooled) consist of the number of papers mentioned and not mentioned in subject category and publication year combinations f. In the 2 × 2 subjectspecific cross table (see Table 2), the cells a f , b f , c f , and d f , are defined as follows:…”
Section: Quantitative Science Studiesmentioning
confidence: 99%